Pengaruh Tingkat Margin, Kualitas Pelayanan Dan Promosi Terhadap Keputusan Nasabah Memilih Pembiayaan Murabahah Usaha Mikro Sektor Dagang (Studi Kasus BPRS Pudurta Insani) - Mashithoh Sitorus; Zuhrinal M. Nawawi; Atika Atika (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
To find out whether margin level, service quality and promotion simultaneously influence customers' decisions on murabahah financing for micro businesses in the trading sector. The type of data used in quantitative data research is primary data sources obtained from questionnaires and interviews with the bank. The objects used in this research are murabahah financing customers of BPRS Puduarta Insani. The results of this research show that Margin Level has a significant effect on Customer Decisions. Based on the value of Tcount > Ttable or 2.988 > 1.66827 and the significant value of the Margin Level variable (X1) is 0.004 > 0.050, it can be concluded that the Margin Level partially has a significant positive effect on customer decisions. Based on the value of Tcount > Ttable or 2.516 > 1.66827 and the significant value of the service quality variable (X2) is 0.003 > 0.050, it can be concluded that service quality partially has a significant positive effect on customer decisions. And promotions have a significant influence on customer decisions. Based on the value of Tcount > Ttable or 2.321 > 1.66827 and the significant value of the Promotion variable is 0.003 > 0.050, it can be concluded that the Promotion Variable partially has a significant positive effect on customer decisions.